Challenges in conducting research on sexual violence and HIV and approaches to overcome them. (3rd May 2017) - Aldous, Annette; Magnus, Manya; Roberts, Afsoon; DeVore, Heather; Moriarty, Theresa; Hatch Schultz, Catherine; Zumer, Maria; Simon, Gary; Ghosh, Mimi
Abstract : Studies have implicated sexual violence as a strong correlate of HIV acquisition in women. Characterizing how such violence affects the female immune system may provide insight into the biological mechanisms of HIV transmission and ultimately improve global HIV prevention strategies. Little research has been carried out in this domain, and the obstacles to investigation can be daunting. Here, we describe methodological challenges encountered and solutions explored while implementing a study of dysregulation of immune biomarkers potentially indicative of increased HIV susceptibility in women following sexual assault. Challenges included accessing sexual assault survivors and defining sexual assault, promoting study participant well‐being during research engagement, reducing selection and information bias, collecting and processing biological samples, and adjusting for confounders such as reproductive tract infections and emotional and physical abuse. We found that many survivors of sexual assault welcomed the attention from study staff and felt empowered by the opportunity to help other women at risk for violence. Well‐trained research staff and well‐articulated community and medical partnerships were key methods to overcoming challenges while promoting the safety and welfare of vulnerable study participants.